Rare Side Effect Due to Vedolizumab in a Patient with Ulcerative Colitis: Catatonic Depression - Durmaz, Ozan; Ozkahraman, Adnan; Kayar, Yusuf (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Durmaz O, Ozkahraman A, Kayar Y. Rare side effect due to vedolizumab in a patient with ulcerative colitis catatonic depression. Turk J Gastroenterol. Published online October 9, 2025. doi:10.5152/tjg.2025.25210.